THE EFFECT OF WAGES AND WORK DISCIPLINE ON WORK PRODUCTIVITY OF PT WAINIBE WOOD INDUSTRY NAMLEA: Pengaruh Upah dan Disiplin Kerja Terhadap Produktivitas Kerja PT Wainibe Wood Industry Namlea) - Buton, Atina; Rumbia, Nuliyati (Uniqbu Journal of Exact Sciences, 2021)
Namlea Wood Industries is a company engaged in the wood and forest product industry and the company always strives to maximize the potential possessed by employees, however, conditions What happens is that the development of employee performance shows that there is a decrease in employee performance, the indication is indicated by: there is a decrease in the amount of production produced by employees. This study aims to determine the effect of wages and work discipline on employee productivity at PT Wainibe Wood Industry Namlea. This study uses Ordinal Probit analysis to analyze the final results, the significant influence between the dependent and independent variables. Based on the results of data processing carried out, testing data using the SPSS 16 program the results obtained for the wage variable are 0.060 and for the work discipline variable are 0.003. The significant value possessed by the wage variable is greater than the set standard value, i.e. it should not exceed 0.005 so that the effect of the wage variable on work productivity has no significant effect. Meanwhile, the work discipline variable has a significant effect.